Prevalence of parasitism and adult survival time of Aedes albifasciatus (Diptera: Culicidae) parasitized by Strelkovimermis spiculatus (Nematoda: Mermithidae) - Di Battista, Cristian (2015)
We described the carryover of Strelkovimermis spiculatus (Poinar and Camino) (Nematoda: Mermithidae) from mosquito larvae, the primary site of maturation, to adults. We analyzed the survival time of male and female Aedes albifasciatus (Macquart) (Diptera: Culicidae) parasitized by S. spiculatus, the time of emergence of nematodes from adult mosquitoes, and the state of parasitism in the same mosquito cohorts during the immature stages. Mosquito larvae with single and multiple parasitism (up to 11 parasites) were observed. The mortality of mosquito larvae and adults was produced in all cases where at least one mermithid emerged. The mortality of S. spiculatus showed an increasing trend in mosquito larvae with larger numbers of nematodes and was higher in larvae parasitized by eight or more nematodes. Maximum survival of parasitized adult females of Ae. albifasciatus was 38 days, while non-parasitized adult males and females survived 39 and 41 days, respectively. Strelkovimermis spiculatus mortality was observed in Ae. albifasciatus larvae with single or multiple parasitisms. The spread of mermithid parasitism in adult mosquito populations is discussed.